Assessment of Nurse’s Knowledge Regarding Physiotherapy for Obesity and Overweight: Penilaian Pengetahuan Perawat tentang Fisioterapi untuk Obesitas dan Kelebihan Berat Badan - Khalaf, Firas Hadi (Academia Open, 2025)
Obesity is a significant global health issue associated with chronic conditions such as cardiovascular disease, type 2 diabetes, and osteoarthritis. Physiotherapy is increasingly recognized as an essential component of multidisciplinary strategies for effective obesity management. However, there is limited research on nurses' knowledge and involvement in utilizing physiotherapy for obesity care. This study aimed to evaluate registered nurses’ understanding of physiotherapy in managing obesity and to identify barriers to its implementation within healthcare settings in Saudi Arabia. A descriptive cross-sectional study was conducted involving 385 registered nurses through an online self-administered questionnaire. The findings revealed that 80.5% of participants correctly identified BMI classifications for obesity, and 65.2% acknowledged physiotherapy as an effective strategy for weight management. Although 72.7% expressed positive attitudes toward physiotherapy, only 38.7% consistently referred obese patients to physiotherapy services. The primary barriers identified were lack of resources (54.5%), time constraints (46.8%), and insufficient knowledge (39.0%). This study is among the first to explore nurses’ perspectives on physiotherapy for obesity within the Saudi healthcare context. The results highlight the importance of implementing targeted educational programs and systemic support to enhance nurses’ competencies, promote effective referral practices, and improve collaborative care for better obesity management outcomes. Highlight: Nurses show high awareness of obesity risks but low referral rates to physiotherapy. Key barriers include limited resources, time constraints, and insufficient training. Emphasizes the need for targeted education to enhance interdisciplinary care. Keyword: Obesity, Overweight,, Physiotherapy, Barriers, Training and education